2004
DOI: 10.1016/j.jcat.2003.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric heating effects on the activity and SO2 resistance of La0.8Ce0.2MnO3 perovskite for methane oxidation

Abstract: Dielectric heating effects on the activity and SO2 resistance of La0.8Ce0.2MnO3 perovskite for methane oxidation Zhang, Y.; Castricum, H.L.; Beckers, J.; Eiser, E.; Bliek, A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…By contrast, the adsorbed SO2 can react with oxygen forming surface sulphites or sulphates, which are stable below their decomposition temperature. Once formed, the reaction can go on in depth following a shell-progressive pathway as discussed elsewhere [1,22].…”
Section: -Effect Of the Nature Of B Metal On Activity And Resistance mentioning
confidence: 99%
“…By contrast, the adsorbed SO2 can react with oxygen forming surface sulphites or sulphates, which are stable below their decomposition temperature. Once formed, the reaction can go on in depth following a shell-progressive pathway as discussed elsewhere [1,22].…”
Section: -Effect Of the Nature Of B Metal On Activity And Resistance mentioning
confidence: 99%
“…[7,14,17] One elegant application is using perovskites as diesel exhaust soot filters. [18,19] By coating a low-loss ceramic monolith with a microwave-susceptible perovskite catalyst, fast and efficient heating is achieved, since all the energy is supplied where it is needed, that is, on the combustion catalyst itself. [20][21][22][23] Perovskite-type oxides, ABO 3 , can be successfully applied as solid "oxygen reservoirs" in redox reactions such as selective hydrogen combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently showed that La 0.8 Ce 0.2 MnO 3 can catalyze the combustion of methane, CO, and synthetic soot using mw irradiation, with a high selectivity towards CO 2 . [9,21,22] The results obtained with the La 0.8 Ce 0.2 MnO 3 catalysts, and our recent success with doped ceria catalysts [23] prompted the search for a mixed perovskite that would combine high oxidation activity and selectivity, high SO 2 tolerance, and high mw susceptibility. In a recent preliminary communication, we demonstrated the feasibility of this approach.…”
Section: Introductionmentioning
confidence: 99%